Cost–effectiveness of screening for DPYD polymorphisms to prevent neutropenia in cancer patients treated with fluoropyrimidines. (June 2016) - Cortejoso, Lucía; García-González, Xandra; García, María I; García-Alfonso, Pilar; Sanjurjo, María; López-Fernández, Luis A
Aim: To compare the cost of screening for three mutations in the dihydropyrimidine dehydrogenase gene and the costs of treating severe fluoropyrimidine-induced neutropenia.Materials & methods: The polymorphisms rs3918290 ( DPYD*2A ), rs67376798 ( DPYD 2846A>T) and rs55886062 (1679T>G, DPYD*13 ) were genotyped using real-time PCR, TaqMan probes and a rapid cell lysis to provide PCR-ready DNA.Results: We found that genotyping 1000 patients in our center cost €6400 and that the mean cost of treating severe neutropenia was €3044. Therefore, if severe fluoropyrimidine-induced neutropenia is reduced by genotyping the three DPYD variations in at least 2.21 cases per 1000 treated patients, then DPYD genotyping will prove cost effective.Conclusion: We demonstrated that real-time DPYD genotyping using TaqMan probes is cost effective in all fluoropyrimidine-based treatments.